IMPLEMENTASI DAN PENGAWASAN PERATURAN DAERAH BERBASIS SYARIAH DI TULUNGAGUNG DAN BLITAR - Anshor, Ahmad Muhtadi; Al Anam, Muhammad Mufti; Ferricha, Dian (Ahkam: Jurnal Hukum Islam, 2020)
This paper aims to examine the implementation, supervision and solutions of sharia-based regional regulations in Tulungagung and Blitar from the philosophical, juridical and sociological aspects. This study is an empirical juridical study. Data are obtained from Tulungagung and Blitar. While the analysis was carried out by using empirical qualitative data analysis methods. The results show that the implementation and supervision of sharia-based regional regulations, primarily related to worship services and respect in carrying out religious values in Tulungagung and Blitar, have been running effectively and efficiently. Keywords: Implementation, Supervision, Regional Regulation, Sharia.